2016
DOI: 10.1159/000446850
|View full text |Cite
|
Sign up to set email alerts
|

Cyclosporine A, a Potential Therapy of Ischemic Reperfusion Injury. A Common History for Heart and Brain

Abstract: Background: Ischemic stroke (IS) and acute myocardial infarction require emergency reperfusion tissue in order to improve functional outcome. Intra-arterial thrombectomy recently showed very encouraging improvement in IS patients' outcome. However, endovascular methods enhancing reperfusion may expose patients to increase in ischemic reperfusion injury. Experimental evidence indicates that brain ischemic reperfusion injury may be attenuated by ischemic pre- and postconditioning. The opening of mitochondrial pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 92 publications
2
21
0
Order By: Relevance
“…In addition, a study found that the inhibition of cyclophilin D attenuated calcium transfer from the endoplasmic reticulum to the mitochondria in ischemiareperfusion injury [29], as accumulated cytosolic calcium can enhance the sensitivity of the mPTP. Moreover, the protection effect of CsA in ischemia injury was also found to be associated with inhibiting the translocation of the nuclear factor of activated T cells or preventing the dephosphorylation of NOS [9,30,31]; however, the specific mechanism remains unknown and further investigation is needed.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a study found that the inhibition of cyclophilin D attenuated calcium transfer from the endoplasmic reticulum to the mitochondria in ischemiareperfusion injury [29], as accumulated cytosolic calcium can enhance the sensitivity of the mPTP. Moreover, the protection effect of CsA in ischemia injury was also found to be associated with inhibiting the translocation of the nuclear factor of activated T cells or preventing the dephosphorylation of NOS [9,30,31]; however, the specific mechanism remains unknown and further investigation is needed.…”
Section: Discussionmentioning
confidence: 99%
“…27 Based on these findings, we propose that there may be a better option to improve cardiac remodeling and outcomes in patient if cyclosporine is orally administered daily after myocardial infarction and during the progression of heart failure. 25,28…”
Section: Discussionmentioning
confidence: 99%
“…However, in patients with proximal cerebral artery occlusion and efficient recanalization, the infarct volume was significantly smaller than the placebo group. Although effectiveness was not confirmed as class I evidence, the study provided hope for larger clinical trials in the future as effectiveness was confirmed in some individuals with stroke …”
Section: Clinical Use Of Csa In the Human Brainmentioning
confidence: 93%
“…There are several neuroprotective agents considered to follow edaravone. Cyclosporine A (CsA), an immunosuppressive agent, is attracting attention as a drug that suppresses mitochondrial dysfunction resulting from the formation of ROS . Like edaravone, CsA's use as a neuroprotective agent has been studied by many Japanese researchers.…”
Section: Introductionmentioning
confidence: 99%